Analysis of the causality between economic growth and government spending: Wagner’s law versus Keynes hypothesis - Yasmin, Yasmin; Sari, Willa Fatika (Universitas Ahmad Dahlan, 2024)
The relationship between economic growth and government spending has been extremely ambiguous over the last few years. In this matter, both Wagner and Keynes expressed their views. However, several research with varying results on those hypotheses. The Keynesian hypothesis, Indonesia's Wagner's law, and the relationship between economic growth and government spending were thus all investigated by the researchers in this study. The Granger causality test and the Engle-Granger cointegration test were used in order to determine the direction with which both variables are linked, as well as a longer-term association. The outcome demonstrated that economic growth and government spending do not have a long-term relationship. In contrast, the causality test revealed a one-way correlation between government spending and economic growth, implying that Wagner's law was applicable in Indonesia. Accordingly, the government must reconsider government spending that is perceived to be less efficient in encouraging economic growth, such as subsidy programs and public goods procurement. Additionally, the government ought to consider reducing government spending and expanding private sector participation in economic development given that Wagner's law has been demonstrated to be applicable in Indonesia.